Hipnoterapi Untuk Mengurangi Hot Flushes pada Perempuan Menopause - aim matun nadhiroh (Jurnal Keperawatan Muhammadiyah, 2021)
Objective:   The most common symptom of menopause is hot flashes. Hot flashes are body heat waves that come on suddenly due to changes in estrogen levels in the upper body and face. This disorder is at risk of developing anxiety to stress, negatively impacting postmenopausal women's social life and quality of life. One of the Mind-Body Interventions to overcome menopause symptoms is hypnosis. Through Hypnotherapy techniques, menopausal women are treated using the art of communication and suggestion that can influence the subconscious to work with the human conscious. The study aimed to analyse the effect of hypnotherapy on reducing hot flashes in postmenopausal women.Methods: This type of research is a Quasi Experiment with a one-group pretest-posttest design approach with the dependent variable being hypnotherapy and the independent variable being hot flashes. Samples were all 33 menopausal people, analysed using the Paired t-test.Results: The results of the study after being tested, the mean pre-test value was 13.67, and the post-test mean value was 21.25, which indicates that the higher the mean value, the decrease in hot flashes before and after hypnotherapy (p<0.001).Conclusion: There is an effect of hypnotherapy on the reduction of hot flashes in menopause. The conclusion is that there is a decrease in hot flushes in menopause before and after hypnotherapy